2018
DOI: 10.1080/21683603.2018.1458357
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and brain evidence for language by ear, mouth, eye, and hand and motor skills in literacy learning

Abstract: Two studies were conducted of students with and without persisting Specific Learning Disabilities (SLDs-WL) in Grades 4 to 9 (M = 11 years, 11 months) that supported the hypotheses that CELF 4 parent ratings for listening (language by ear), speaking (language by mouth), reading (language by eye), and writing (language by hand) were correlated with both (a) normed, standardized behavioral measures of listening, speaking, reading, and writing achievement (Study 1, 94 boys and 61 girls); and (b) fMRI connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, the 3-day delayed memory in the two hand movement conditions remained the same as the 25-minute delayed memory, unlike in the other three conditions, in which memory after 3 days was poorer than in the immediate and 25-minute recall. Consistent with the findings of previous studies (Berniger et al, 2019;Habib et al, 2003;Propper et al, 2013), moving the hands during the encoding stage enhanced learning and memory performance, and our findings showed that the effect on memory is sustainable for at least 3 days. Body movements, such as moving the hands (Propper et al, 2013) and chewing (Hirano et al, 2008), activate the frontal brain areas related to memory and may facilitate information consolidation during the encoding stage and thus improve memory.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the 3-day delayed memory in the two hand movement conditions remained the same as the 25-minute delayed memory, unlike in the other three conditions, in which memory after 3 days was poorer than in the immediate and 25-minute recall. Consistent with the findings of previous studies (Berniger et al, 2019;Habib et al, 2003;Propper et al, 2013), moving the hands during the encoding stage enhanced learning and memory performance, and our findings showed that the effect on memory is sustainable for at least 3 days. Body movements, such as moving the hands (Propper et al, 2013) and chewing (Hirano et al, 2008), activate the frontal brain areas related to memory and may facilitate information consolidation during the encoding stage and thus improve memory.…”
Section: Discussionsupporting
confidence: 93%
“…As the M1 area is far easier to be located than classical language areas such as Broca’s area, this finding highlighted a potentially practical way to “kill two birds with one stone”, in treating the language and motor impairments of patients with stroke. However, although the structural and functional connectivity have been identified between the brain’s language and motor areas in healthy volunteers and the patients with various neurological disorders [ 10 , 11 , 12 , 13 ], it is still not clear if and how the NIBS targeting the M1 would affect the language function via these connections. Therefore, we conducted this preliminary functional MRI study to investigate the immediate brain functional effects of the left M1 stimulation with intermittent theta-burst stimulation (iTBS), which is a popular TMS method, in treating PSA using resting-state functional magnetic resonance (fMRI) images.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, inadequate literacy capacity can lead to mental health decline (Bonifacci et al, 2020) or limit vocational prospects (McCloskey & Rapp, 2017). Consequently, early school or writing experiences can influence a child's developing identity and self‐efficacy (Berninger et al, 2019). Accordingly, the results of this study evidence a symbiosis between writing and identity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this study was designed as an attempt to fill this gap by exploring the experiences of young people aged 10–14 years diagnosed with dysgraphia in Australia. However, as children with dysgraphia might be considered vulnerable due to an increased risk for depression and anxiety (Berninger et al, 2019; Bonifacci et al, 2020), the researchers chose to employ an art‐based, phenomenological methodology (Betensky, 1995; Kalenjuk et al, 2022). The art‐based approach coupled with semi‐structured interviews were considered a sensitive and age‐appropriate way to generate data (Northall et al, 2020; Shosha, 2012).…”
Section: Introductionmentioning
confidence: 99%